Collaborative desing in web aplication development to improve tuberculosis diagnostic - Palomino Vidal, Carlos Efraín (2023)
In Peruvian Tuberculosis Reference Laboratory of the Regional Health Directorate of Callao, issues related to the diagnostic process where identified, because of the slowly generations of patients result. This research develops a web application to solve these issues using a participatory design. Qualitative data were recollected through interviews and focus groups in 45 medical centers belong to the regional health directorate (DIRESA) from Callao. These data were used to define the correct design and develop the required processes in the web application. Quantitative data were recollected either, to measure the efficiency of the new diagnostic process using the web application. The results show that with the use of the web application 120 hours were reduce from the monthly validation results and avoid the generation of 8,700 duplicate information, with these results the diagnostic process was improve. The research also confirms that the design and use of technological tools in a collaborative environment improve the process efficiency.